Comparative studies of vibration control effects between structures with particle dampers and tuned liquid dampers using substructure shake table testing methods. Issue 121 (June 2019) - Fu, Bo; Jiang, Huanjun; Wu, Tao
Abstract: This paper compares the vibration control performance of particle dampers (PDs) and tuned liquid dampers (TLDs) by using the up-to-date substructure shake table testing (SSTT) method. In implementing the SSTT, three representative model-based integration algorithms, whose algorithmic parameters are functions of the complete model of the structure system to enable unconditional stability to be achieved within the framework of an explicit formulation, are adopted. The experimental procedures of the SSTT methods using the three integration algorithms are presented. The SSTT system of the single-degree-of-freedom (SDOF) structures with PDs/TLDs is constructed and verified by comparing the experimental results of the SSTTs and the corresponding complete structure shake table tests. The vibration reduction effects of PDs and TLDs with the same mass ratio are investigated and compared by conducting a series of SSTTs of the SDOF systems with such devices under the excitation of ground motion. The influences of mass ratio, damping ratio and structural frequency on control efficiency of PDs and TLDs are studied. The results from the parametric analyses demonstrate that all the aforementioned factors have significant impacts on the vibration control performance of both dampers. Most experimental results indicate that the PDs have better vibration control performance than the counterpart TLDs. Highlights: The SSTT methods for the SDOF structure-PD/TLD system using three model-based integration algorithms are proposed. The SSTT experimental platform for the SDOF structure-PD/TLD system is constructed and verified. The vibration reduction effects of PDs and TLDs with the same mass ratio are investigated and compared. The influences of mass ratio, damping ratio and structural frequency on control efficiency of PDs and TLDs are studied.